2021
DOI: 10.3389/fgene.2021.695597
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Gene Networks Regulated by U11 Small Nuclear RNA in Bladder Cancer

Abstract: Small nuclear RNA is a class of non-coding RNA that widely exist in the nucleus of eukaryotes. Accumulated evidences have shown that small nuclear RNAs are associated with the regulation of gene expression in various tumor types. To explore the gene expression changes and its potential effects mediated by U11 snRNA in bladder cancer cells, U11 snRNA knockout and overexpressed cell lines were constructed and further used to analyze the gene expression changes by RNA sequencing. The differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Wang et al. found that U11 may be involved in the regulation of gene expression in bladder cancer cells, which can alter gene expression by affecting the PI3K-Akt signaling pathway and may be a potential biomarker for the clinical diagnosis and treatment of bladder cancer ( 28 ). In other systems, Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al. found that U11 may be involved in the regulation of gene expression in bladder cancer cells, which can alter gene expression by affecting the PI3K-Akt signaling pathway and may be a potential biomarker for the clinical diagnosis and treatment of bladder cancer ( 28 ). In other systems, Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…After snoRNAs recognize and bind the complementary sequence on the target rRNA, and they send a signal to the paired protein for accurate base modification to play an important regulatory function under a variety of physiological and pathological conditions ( 24 ). Nuclear small RNA (snRNA) is a kind of small molecular RNA with a length of 100-215 nt in the eukaryotic genome that exists in the nucleus ( 28 ). SnRNA is highly conserved, the content is small in cells, and the expression is spatiotemporally specific ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, noncoding RNAs have been identified as potential biomarkers for bladder cancer prognosis (165,166). Besides lncRNAs, miRNAs and circRNAs, one study showed that PIWI-interacting RNAs (piRNAs) and snRNAs are important in bladder carcinogenesis (167,168). In this work, it has been shown that 106 piRNAs were increased and 91 piRNAs were decreased in bladder tumor specimens.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 75%
“…Several studies have shown that some snRNP particles regulate migration, invasion and gene regulation in multiple tumor cell lines. 45 , 46 However, the complete understanding of snRNP particles in tumors is still far from satisfactory. RN7SK is a 331 nt snRNA transcribed by RNA polymerase III.…”
Section: Discussionmentioning
confidence: 99%